Prematuridad en el hospital de apoyo N° 2 yarinacocha-Región Ucayali-Perú periodo julio 1994 a junio 1995” - Reategui Lozano, Jessy (1996)
The birth of preterm or premature is that whose gestational age at birth is among the 20-36 weeks, calculated from the date of the last menstrual period. The present study tipo\ descriptive with collection prospective of data, \se performed in the Hospital's support NQ 2 Yarinacocha-Pucallpa, during e ~ period of July 1,994 to June 1,995; in order to determine the factors associated with prematurity; After a statistical analysis of the data, it was concluded that these are: age mother less than 21 years, the occupation housewife, civil esta.do ' maiden, birth period of less than 2 years, maternal anaemia, to ~ edentes of abortion and birth of pretermin9 pr-delivery excluded, in the pathologies of break prematur-membranes, urinary tract infection and ~ emorr-agia in the third trimestr-e; being the causes of mor-bimortalidad perinatal asphyxia and sepsis. We recommend is try of raise the level socio-economic of the population, encourage the control prenatal...